A Comparative Analysis Of Linear And Nonlinear Loads On The Performance Of Three-Phase Synchronous Generators - Yoas Anggi Gresdeo Pasaribu; Solly Aryza; Muhammad Erpandi Dalimunthe (Jurnal Scientia, 2024)
This Study Aims To Analysed And Compare The Effects Of Linear And Nonlinear Loads On The Performance Of A Three-Phase Synchronous Generator. Linear Loads, Characterized By A Proportional Relationship Between Voltage And Current, And Nonlinear Loads, Which Produce Harmonic Distortion In Current And Voltage, Can Affect The Stability And Efficiency Of Generator Operation. In This Study, Various Loading Scenarios Were Tested Using A Software-Based Simulation Model. The Results Of The Analysis Show That Nonlinear Loads Cause A Significant Increase In Harmonic Distortion In The System, Which Has The Potential To Reduce The Efficiency And Operational Life Of The Generator. In Contrast, Linear Loads Tend To Produce More Stable And Efficient Generator Performance. These Findings Provide Important Insights Into The Design And Selection Of Appropriate Loads To Maintain Optimal Performance Of Three-Phase Synchronous Generators.